THE EFFECTIVENESS OF RME AND SCIENTIFIC APPROACHES IN TERMS OF MATHEMATICAL LITERACY AND LEARNING INTEREST - Shinta Bella Margaretta; Sri Andayani; Wahyu Setyaningrum (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Comparative studies on the effectiveness of the RME and scientific approaches in improving mathematical literacy and learning interest remain limited, especially at the JHS level. This study examines the effectiveness of each approach and compares their impact on students’ mathematical literacy and learning interest. A quantitative method with a pretest posttest control group design was used, involving 64 seventh-grade students from a public JHS in Yogyakarta, selected through convenience sampling. The experimental group received RME-based instruction, while the control group was taught using the scientific approach. MANOVA results show that both approaches significantly improve mathematical literacy and learning interest. However, no significant difference was found between the two groups, as indicated by a p-value > 0.05. These findings suggest that both approaches are equally effective. The study provides insight for teachers in applying context-based learning. Future research may explore digital-based strategies to further support mathematical literacy and learning interest.